Population genomic structure of killer whales (Orcinus orca) in Australian and New Zealand waters. Issue 1 (22nd July 2021) - Reeves, Isabella M.; Totterdell, John A.; Barceló, Andrea; Sandoval‐Castillo, Jonathan; Batley, Kimberley C.; Stockin, Karen A.; Betty, Emma L.; Donnelly, David M.; Wellard, Rebecca; Beheregaray, Luciano B.; Möller, Luciana M.
Abstract: Population genomic data sets have enhanced power to detect cryptic and complex population structure and generate valuable information for the conservation and management of wildlife species. Globally, killer whales ( Orcinus orca ) are considered to have a complex population structure due to their ability to specialize in a variety of ecological niches. In the Australasian region, they are found year round in New Zealand waters and are sighted in all Australian waters, with seasonal aggregations in the northwest (NWA) and southwest (SWA). Regionally, there is some knowledge regarding killer whale abundance, diet, acoustics, and social structure, but limited information about their population structure. Here, we present a population structure assessment of Australasian killer whales using 17, 491 high quality genome‐wide single nucleotide polymorphisms (SNPs), combined with sequences of the mitochondrial DNA control region. The results indicate a minimum of three populations: New Zealand, NWA, and SWA. These populations present moderate levels of genomic diversity, negligible levels of inbreeding, small effective population sizes, and low contemporary migration rates among them. Mitochondrial DNA analysis elucidated five closely related haplotypes, suggestive of matrilineal societies, consistent with killer whales elsewhere. This information will assist conservation management of killer whales in the Australasian region.